Implementation Expert System for Diagnosing Tuberculosis Using Dempster-Shafer Method - Jenal Sapdana; Yunan Henryanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
Tuberculosis (pulmonary TB) is still a frightening disease for the world community, especially in Indonesia. This expert system application for the diagnosis of Tuberculosis is a computerized system to assist doctors and the public in diagnosing Tuberculosis. Efforts that can be made are to provide the best information to patients or the public about Tuberculosis disease through consultation with experts or using expert system applications. So for this reason, an application is designed that can provide expert information about Tuberculosis as a substitute for an expert or doctor. The purpose of this research is to build a web-based expert system for the diagnosis of tuberculosis. The stages carried out in this research are preliminary studies, identification of problems in which problems are found in expertise or designing an expert system, then literature study, the process of diagnosing symptoms and diseases by collecting data, if fulfilled then proceed with making a rule base and designing system. After completion, proceed to the testing and implementation phase to find out the system is feasible to use and in accordance with the design, then evaluate the results and report and finish. Based on the results of research and testing of the implementation of an expert system for diagnosing tuberculosis using the web-based Dempster-Shafer method that has been carried out by the author, several conclusions can be drawn, namely; This expert system created successfully performs data processing and provides disease results from the selected symptoms using the Dempster-Shafer method, the application is built using the PHP programming language and is supported by visualization languages ​​such as HTML, CSS, JQuery and MySQL as databases, as well as system applications. Experts who are built can make it easier for people with tuberculosis and health parties to diagnose using the Dempster-Shafer method.